Sororin pre‐mRNA splicing is required for proper sister chromatid cohesion in human cells. (4th August 2014) - Watrin, Erwan; Demidova, Maria; Watrin, Tanguy; Hu, Zheng; Prigent, Claude
Abstract Sister chromatid cohesion, which depends on cohesin, is essential for the faithful segregation of replicated chromosomes. Here, we report that splicing complex Prp19 is essential for cohesion in both G2 and mitosis, and consequently for the proper progression of the cell through mitosis. Inactivation of splicing factors SF3a120 and U2AF65 induces similar cohesion defects to Prp19 complex inactivation. Our data indicate that these splicing factors are all required for the accumulation of cohesion factor Sororin, by facilitating the proper splicing of its pre‐mRNA. Finally, we show that ectopic expression of Sororin corrects defective cohesion caused by Prp19 complex inactivation. We propose that the Prp19 complex and the splicing machinery contribute to the establishment of cohesion by promoting Sororin accumulation during S phase, and are, therefore, essential to the maintenance of genome stability.